INTEGRATION OF BIM AND E-PROCUREMENT IN THE CONSTRUCTION INDUSTRY: A SYSTEMATIC BIBLIOGRAPHIC REVIEW - Schaker, Felipe Ricardo Carvalho; Santos, Adriana de Paula Lacerda (Revista Latino-Americana de Inovação e Engenharia de Produção, 2016)
ABSTRACT: The procurement process virtualization tend to reduce transaction costs and expand supply chains, especially through e-procurement platforms. Concurrent advances in information and communication technologies such as Building Information Modeling (BIM) have proved to improve the typically hindered information flow of the construction industry. The aim of this research is to assess the current state of the art of the integration of BIM and the e-procurement process. Fifteen papers were correlated through a Systematic Bibliographic Review (SBR) and the result reveals real possibilities of integration of BIM and e-procurement. Great benefits can result from the integration, such as reduction of the fragmentation in this industry. However, there are still various barriers to overcome, mainly about the civil construction industry fragmentation and the systems interoperability. The most advanced researches were developed in Portugal, where there is a strong governmental foment for the e-procurement utilization. The government is recognized as the most influential agent for the effective implementation of e-procurement platforms, even more strongly than the role of the companies that will run this process. Keywords: E-procurement; BIM; Systematic Bibliographic Review. RESUMO: A virtualização do processo de aquisição tende a reduzir custos de transação e ampliar cadeias de suprimento, especialmente através de plataformas de e-procurement. Avanços paralelos nas tecnologias de informação e comunicação, como Building Information Modeling (BIM) provaram melhorar o fluxo de informação normalmente falho da indústria da construção. O objetivo desta pesquisa é avaliar o estado da arte da integração entre BIM e e-procurement. Quinze artigos foram correlacionados através de uma revisão bibliográfica sistemática e o resultado revela possibilidades reais de integração entre BIM e e-procurement. Grandes benefícios podem resultar da integração, tais como a redução da fragmentação nesta indústria. No entanto, ainda existem diversas barreiras a superar, principalmente quanto à fragmentação da indústria da construção civil e à interoperabilidade dos sistemas. As pesquisas mais avançadas foram desenvolvidas em Portugal, onde há um forte fomento governamental para a utilização de e-procurement. O governo é reconhecido como o agente mais influente para a efetiva implementação de plataformas de e-procurement, com papel ainda mais forte do que o das empresas que serão executoras deste processo. Palavras-chave: E-procurement; BIM; Revisão bibliográfica sistemática. RESUMEN: La virtualización del proceso de adquisición tiende a reducir los costos de transacción y ampliar las cadenas de suministro, especialmente a través de las plataformas e-procurement. Avances paralelos en las tecnologías de la información y la comunicación, como Building Information Modeling (BIM) han demostrado mejorar el flujo de información normalmente fallo de la industria de la construcción. El objetivo de esta investigación es evaluar el estado actual de la integración de BIM y e-procurement. Quince artículos se correlacionaron través de una revisión bibliográfica sistemática y el resultado revela posibilidades reales de integración. Grandes beneficios pueden ser el resultado de la integración, como la reducción de la fragmentación en esta industria. Sin embargo, hay varias barreras que superar, sobre todo acerca de la fragmentación del sector de la construcción civil y la interoperabilidad de los sistemas. Las investigaciones más avanzadas se han desarrollado en Portugal, donde hay un fuerte fomento gubernamental para la utilización de e-procurement. El gobierno es reconocido como el agente más influyente para la aplicación efectiva de las plataformas e-procurement, incluso con papel más fuerte que el de las empresas que van a ejecutar este proceso. Palabras clave: E-procurement; BIM; Revisión bibliográfica sistemática.